Protecting healthcare workers from COVID-19: learning from variation in practice and policy identified through a global cross-sectional survey. (21st May 2020) - Hussain, Zaamin B.; Shoman, Haitham; Yau, Peter W. P; Thevendran, Gowreeson; Randelli, Filippo; Zhang, Mingzhu; Kocher, Mininder S.; Norrish, Alan; Khanduja, Vikas
Abstract : Aims: The COVID-19 pandemic presents an unprecedented burden on global healthcare systems, and existing infrastructures must adapt and evolve to meet the challenge. With health systems reliant on the health of their workforce, the importance of protection against disease transmission in healthcare workers (HCWs) is clear. This study collated responses from several countries, provided by clinicians familiar with practice in each location, to identify areas of best practice and policy so as to build consensus of those measures that might reduce the risk of transmission of COVID-19 to HCWs at work. Methods: A cross-sectional descriptive survey was designed with ten open and closed questions and sent to a representative sample. The sample was selected on a convenience basis of 27 senior surgeons, members of an international surgical society, who were all frontline workers in the COVID-19 pandemic. This study was reported according to the Standards for Reporting Qualitative Research (SRQR) checklist. Results: Responses were received by all 27 surgeons from 22 countries across six continents. A number of the study respondents reported COVID-19-related infection and mortality in HCWs in their countries. Differing areas of practice and policy were identified and organized into themes including the specification of units receiving COVID-19 patients, availability and usage of personal protective equipment (PPE), other measures to reduce staff exposure, and communicating with and supporting HCWs. Areas more specific to surgery also identified some variation in practice and policy in relation to visitors to the hospital, the outpatient department, and in the operating room for both non-urgent and emergency care. Conclusion: COVID-19 presents a disproportionate risk to HCWs, potentially resulting in a diminished health system capacity, and consequently an impairment to population health. Implementation of these recommendations at an international level could provide a framework to reduce this burden.